Administration, legal and financial problems in the iraqi tax system - Ali Abdi, Zainab; Sulaiman Yasin Al-Safar, Ahmed (Humanities Journal of University of Zakho, 2023)
This study aims to explain the tax structure in Iraq and to report each type of tax, as well as to identify the administrative, legal and financial problems that this system suffers from and to try to find solution to them. The research relied on the inductive method using the analytical approach. The study reached a number of conclusions, including: it was found through the research the validity of the hypothesis that was adopted is correct, which is that addressing the problems that the tax system suffers from will contribute to increasing tax revenue, and one of the most important problems that any administration suffers from is the lack of trust between the tax administration and the taxpayer, and it depends on the tax structure in Iraq which is largely based on indirect taxes, and reliance on old and non- renewable legislation that does not meet the increases in expenditures, and that tax evasion of various types results in negative economic, social and psychological effects in society. Plus, the contribution of taxes in financing the budget is low in Iraq. This is because the state relies mainly in financing expenditures on oil and its revenues.